Two encounters with the cultural other: Paulo Coelho's A Bruxa de Portobello and its English translation - Marques Pimentel, Sarah-Leah (My University, 2009)
ABSTRACT This study recognises the need for greater cultural interaction in a globalised world in which cultural identities are no longer contained within national borders. The aim of this dissertation is, therefore, to address concerns arising from the role played by literary translation as a cultural mediator within contemporary societies. The theoretical framework is drawn from the concept of an “in-between space” in the work of the post-colonial theorist, Homi Bhabha (1990, 2005), and Emmanuel Levinas‟s (1991, 1993) understanding of the relationship between the self (the Same) and an external other (the Other). The relevance of these theoretical concepts to the field of translation studies is explored and these are then practically applied to A Bruxa de Portobello (2006), a novel written by a contemporary Brazilian author, Paulo Coelho, and its English translation (2007). The analysis of the two novels considers the ways in which otherness is presented in both texts, from which conclusions are drawn showing that literary translation can be used as an instrument to promote greater cultural understanding.